Bridging the Gap between Collection and Analysis: Intelligence Information Processing and Data Governance - Palfy, Arpad (International journal of intelligence and counterintelligence, 2015)
Whether dealing with networks of organized criminals, war criminals, corrupt officials, or terrorist groups, the capacity of any organization to integrate and understand the intelligence it already has with the information it collects plays a key role in its ability to achieve intelligence successes. Bridging this pervasive gap between an organization's collection and analytical capabilities is critical if security organizations are to maximize their knowledge discovery and knowledge generation capacities within existing technological and human resource boundaries. Consequently, developing such a knowledge integration capability becomes all the more important if their goal is to overcome the combined challenges of exponential increases in information with the requirement to produce timely, accurate, and actionable analytical products.